Comparison of the Direct Effects of Human Adipose- and Bone-Marrow-Derived Stem Cells on Postischemic Cardiomyoblasts in an In Vitro Simulated Ischemia-Reperfusion Model. (19th June 2013) - Szepes, Mónika; Benkő, Zsolt; Cselenyák, Attila; Kompisch, Kai Michael; Schumacher, Udo; Lacza, Zsombor; Kiss, Levente
Abstract : Regenerative therapies hold a promising and exciting future for the cure of yet untreatable diseases, and mesenchymal stem cells are in the forefront of this approach. However, the relative efficacy and the mechanism of action of different types of mesenchymal stem cells are still incompletely understood. We aimed to evaluate the effects of human adipose- (hASC) and bone-marrow-derived stem cells (hBMSCs) and adipose-derived stem cell conditioned media (ACM) on the viability of cardiomyoblasts in an in vitro ischemia-reperfusion (I-R) model. Flow cytometric viability analysis revealed that both cell treatments led to similarly increased percentages of living cells, while treatment with ACM did not (I-R model: 12.13 ± 0.75 %; hASC: 24.66 ± 2.49 %; hBMSC: 25.41 ± 1.99 %; ACM: 13.94 ± 1.44 %). Metabolic activity measurement (I-R model: 0.065 ± 0.033 ; hASC: 0.652 ± 0.089 ; hBMSC: 0.607 ± 0.059 ; ACM: 0.225 ± 0.013 ; arbitrary units) and lactate dehydrogenase assay (I-R model: 0.225 ± 0.006 ; hASC: 0.148 ± 0.005 ; hBMSC: 0.146 ± 0.004 ; ACM: 0.208 ± 0.009 ; arbitrary units) confirmed the flow cytometric results while also indicated a slight beneficial effect of ACM. Our results highlight that mesenchymal stem cells have the same efficacy when used directly on postischemic cells, and differences found between them in preclinical and clinical investigations are rather related to other possible causes such as their immunomodulatory or angiogenic properties.